Stable oxygen isotope (d18O), Mg/Ca and temperature records of foraminiferal species (G. bulloides, N. incompta, Uvigerina spp., C. wuellerstorfi, M. barleeanum) of core SO264_45-2 in sediment depth 6.03-8.32 m - Lara Jacobi; Dirk Nürnberg; Weng-si Chao; Lester Lembke-Jene; Ralf Tiedemann (PANGAEA, 2023)
Stable oxygen isotope (δ18O) measurements were performed on the benthic foraminiferal species C. wullerstorfi, Uvigeringa spp., and M. barleeanum as well as on the planktic foraminiferal species G. bulloides and N. incompta. Additionally Mg/Ca-measurements were performed on the two planktic species. The foraminiferal specimens were selected from gravity core SO264-45-2, which was recovered from Jimmu Seamount (46.5632°N 169.601211°E) from 2425 m water depth during R/V SONNE cruise SO264 (SONNE-EMPEROR) in August 2018. Sampling and analytical studies were carried out from 6.03 m – 8.32 m core depth at 2-4 cm spatial resolution. The isotope analyses were performed on a Thermo Scientific MAT 253 mass spectrometer with an automated Kiel IV carbonate preparation device. Trace metal analyses were performed on a VARIAN 720-ES Axial ICP-OES, a simultaneous, axial-viewing inductively coupled plasma - optical emission spectrometer coupled to a VARIAN SPS3 sample preparation system. Both systems were operated at GEOMAR. The proxy data provide stratigraphical information and were used to calculate water temperature and the ice volume-corrected δ18O of seawater. Contaminant phases of the trace metal analyses were added (Al/Ca, Fe/Ca, Mn/Ca in mmol/mol).